PENDIDIKAN AKAL DALAM PERPEKTIF IBN RUSYD - M. Nasihuddin (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2019)
Ibn Rusyd was born and grew up in an environment of philosophers and state digniteries, this factor turns out to have shaped Ibn Rusyd to be come a philosopher and as a commentator an Aristoteles. He was one of the most fluential philosophers, not only in the Islamic world but also in the western world. He succeeded in spreading new ideas by giving people freedom ofv the thought through their rational abilities. His controversial ideas are proven by his work that tries to bring reason to religion and philosophy with revelation, making it possibl for humans to have deep fait and have high knowledge. For Ibn Rusd to use of reasoning in an effort to understand the universe and the hidden meaning of revelation is part of the function of revelation it self because in the Qur’an contains instructions realitions to the activity of reason.